An integrated research framework combining genomics, systems biology, physiology, modelling and breeding for legume improvement in response to elevated CO2 under climate change scenario - Palit, Paramita; Kudapa, Himabindu; Zougmoré, Robert B.; Kholová, Jana; Whitbread, Anthony M.; Sharma, Mamta; Varshney, Rajeev K. (Elsevier, 2020)
How unprecedented changes in climatic conditions will impact yield and productivity of some crops and theirresponse to existing stresses, abiotic and biotic interactions is a key global concern. Climate change can also alternatural species’abundance and distribution or favor invasive species, which in turn can modify ecosystem dy-namics and the provisioning of ecosystem services. Basic anatomical differences in C3and C4plants lead to theirvaried responses to climate variations. In plants having a C3pathway of photosynthesis, increased atmosphericcarbon dioxide (CO2) positively regulates photosynthetic carbon (C) assimilation and depresses photorespira-tion. Legumes being C3plants, they may be in a favorable position to increase biomass and yield through variousstrategies. This paper comprehensively presents recent progress made in the physiological and molecular at-tributes in plants with special emphasis on legumes under elevated CO2conditions in a climate change scenario.A strategic research framework for future action integrating genomics, systems biology, physiology and cropmodelling approaches to cope with changing climate is also discussed. Advances in sequencing and phenotypingmethodologies make it possible to use vast genetic and genomic resources by deploying high resolution phe-notyping coupled with high throughput multi-omics approaches for trait improvement. Integrated crop mod-elling studies focusing on farming systems design and management, prediction of climate impacts and diseaseforecasting may also help in planning adaptation. Hence, an integrated research framework combining geno-mics, plant molecular physiology, crop breeding, systems biology and integrated crop-soil-climate modelling willbe very effective to cope with climate change.